Dinamika Konsep Kapita Selekta Pendidikan Agama Islam - Nadeak, Hasanah (Jurnal Pendidikan Agama Islam, 2024)
Often the meaning of "selected capital" is confused due to various internal and external variables, including various scientific perspectives, shifting social standards, and local cultural influences. This raises a discussion about the meaning of "selected capital" and how it should contribute in relation to Islamic education. A deeper understanding of Islam can be hampered by a vague understanding of "selected capital". The purpose of this study is to determine the dynamics of the concept of select capital in Islamic Religious Education To better understand the role played by "selected capital" in religious teaching and how it influences the attitudes and actions taken by Muslims in everyday life. This study is important to explain the sociological approach in Islamic studies. By gaining a comprehensive understanding of sociological values ​​in Islamic studies, including the scope and issues that exist. This study uses a qualitative approach, especially by using the library research method The discussion method in this study uses a descriptive analytical approach, which aims to provide explanations and connect key ideas or concepts related to the topic being studied. The crisis of religious values, understanding of what is meant by a good life. The Increasing Shift Towards Pragmatism, Towards Materialism and Individualism, Are some of the internal factors that cause selective capital changes in education, especially in Islam. The concept of character education in Islamic education does not only teach morality (right and wrong); but also emphasizes the importance of acting morally.